PRESENT STATE OF THE SPRING PLANKTON COMMUNITY IN THE NORTHERN OKHOTSK SEA (1997–2017) - A. F. Volkov (Известия ТИНРО, 2018)
Two periods are clearly distinguished within the last two decades (1997–2017) by several quantitative parameters of the plankton community in the northern shelf zone of the Okhotsk Sea: the period of high productivity in the 1997–2005 with the biomass of 1000–1200 mg/m3 and the period of medium productivity in the 2006–2017 with the biomass of 550–580 mg/m3. The sharp drop of the biomass had occurred in just one year because of decreasing of the large-sized zooplankton abundance (euphausiids, mysids, hyperiids, and pteropods) that formed the bulk of the food base for commercial species of nekton. After the drop, the plankton biomass had stabilized again. The similar decreasing was observed earlier, in 1998, as the result of several warm years, but in those times the zooplankton abundance restored its maximal values in 2 years. Correlations of the large-sized zooplankton dynamics with the thermal parameters, as the cold subsurface layer temperature and the maximum and mean values of the ice cover are considered. Generally, the period of high productivity was distinguished by cold environments, and they were warmer in the period of medium productivity.